Klasifikasi Kepuasan Pelanggan Menggunakan Metode Classification and Regression Tree (CART) - Safitri, S. Thya; Wiguna, Citra; Kusumawardani, Dwi Mustika; Wibowo, Intan Yulita (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Customer satisfaction in an application technology has an influence on the value of information technology applications. The use questionnaire method is used to measure the usability of information technology applications through aspects of usefulness, ease of use, ease of learning and satisfaction. Net Promoter Scale is a measuring tool that is widely used to measure customer satisfaction in an organization. The problem that often occurs is that when the organization takes the NPS measurement, the factors that significantly influence the NPS value are not yet known. The e-boarding application developed by PT Kereta Api Indonesia is an application that is very helpful for train passengers during boarding. However, this convenience has not been widely used by passengers using the rail transportation mode. PT Kereta Api Indonesia Persero needs to know the value of the NPS of the e-boarding application as a means of measuring customer satisfaction with the developed information technology application. The classification method uses the Classification and Regression Tree (CART) to identify the linkages between the e-boarding usability measurement aspects using a use questionnaire against the final NPS score. The purpose of this calcification is to determine the factors that affect the usability aspect of the NPS value in the KAI Access e-boarding application. The results of this study indicate that the e-boarding application has an NPS value of 42% or a GOOD value. The more customers who behave as Promoters, the higher the NPS value will be. The CART classification that has been carried out shows that to become a Promoters, the e-boarding application must have a high value of ease of learning and satisfaction.